Mental disorders in adults from Ribeirão Preto, Brazil: a cross-sectional analysis of two birth cohorts - Luis Felipe Scarabelot; Jesem Douglas Yamall Orellana; Viviane Cunha Cardoso; Marco Antonio Barbieri; Ricardo Carvalho Cavalli; Heloisa Bettiol; Bernardo Lessa Horta; Cristina Marta Del-Ben (BMC, 2024)
Abstract Background In Brazil, the prevalence of mental disorders is heterogeneous, with most studies conducted in large cities with high population density. This study aimed to assess the prevalence of mental disorders and psychiatric comorbidities among young adults (22-23 years old) and adults (37-38 years old) from Ribeirão Preto, a city located in the Northeast of the São Paulo state, with approximately 700,000 inhabitants, and to explore associations with sociodemographic variables, suicide risk, and health service usage. Second, we aimed to evaluate the performance of the Self-Report Questionnaire (SRQ-20) as a screening tool for mental disorders to be applied to the local population. Methods Participants from the 1978/1979 and 1994 Ribeirão Preto birth cohorts were evaluated using the Mini International Neuropsychiatric Interview (MINI) and the SRQ-20 at mean ages of 22-23, and 37-38 years, respectively. Results Our sample comprised 1,769 individuals from the 1978/1979 cohort and 1,037 from the 1994 cohort. The prevalence of mental disorders ranged from 28.6% (1978/79) to 31% (1994), with frequent comorbid diagnoses (42.7% and 43.3%, respectively). Men and women had a similar prevalence of mental disorders in the younger cohort, while women had a higher prevalence in the older cohort. Low educational attainment was associated with higher rates of diagnosis. In both cohorts, alcohol and other psychoactive substance use was higher among those with a psychiatric diagnosis. Although those with a psychiatric diagnosis were less satisfied with their own health, only one-fifth had seen a mental health professional in the previous year. A psychiatric diagnosis increased the suicide risk by 5.6 to 9.1 times. Regarding the SRQ-20, the best cutoff points were 5/6 for men and 7/8 for women, with satisfactory performance. Conclusions The prevalence and comorbidity of mental disorders were high in both cohorts and comparable to those in larger Brazilian cities. However, few individuals with a diagnosis had sought specialized care. These data suggest that the mental health gap is still significant in Brazil.